Inovasi Modul Monitoring Parameter Listrik Pada PHB-TR 400/230V Berbasis Mikrokontroller - Rahma Nur Amalia; Ika Noer Syamsiana; Tresna Umar Syamsuri; Ana Mardiana (Elposys: Jurnal Sistem Kelistrikan, 2024)
The reliability of electrical energy distribution is paramount to continuously meet consumer demands. Effective maintenance of the distribution system, particularly the low voltage switchgear (PHB-TR), is essential to ensure this reliability. A significant challenge arises from the fact that many distribution substations are situated in remote or hard-to-access locations, complicating the maintenance process for technicians. This study aims to design and develop an innovative module for monitoring current and voltage, utilizing the Arduino Nano microcontroller, equipped with a PZEM sensor module and an I2C LCD display. The primary objective is to facilitate remote monitoring and enhance the efficiency of maintenance operations at these substations. The research methodology encompasses the design, simulation, and testing phases of the monitoring module applied to a 400/230 V PHB-TR. The module's performance was evaluated based on its accuracy in measuring current and voltage. The findings indicate that the developed module exhibits high accuracy, with an average current sensor error margin of 2.9% and a voltage sensor error margin of 1.3%. The implications of this research are significant for the field of electrical distribution maintenance. The implementation of this monitoring system can lead to substantial improvements in time and energy efficiency, as well as enhanced safety for maintenance personnel. Moreover, it facilitates real-time remote monitoring, which is particularly beneficial for substations located in challenging terrains. This innovation holds the potential to streamline maintenance processes and ensure a more reliable supply of electrical energy to consumers.